Results 1 to 2 of 2
  1. #1
    Join Date
    Apr 2006

    Multi valued dependency proof

    Hello! My first post here, hope you guys can help me out!

    Ok. I'm doing an assignment on database relations theory. One of the tasks is to prove that the following statement regarding multivalued dependencies holds:

    If X ->-> Y and Y ->-> Z then X ->-> Y/Z (equiv to X ->-> Y - Z),

    which is called the transitivity rule.

    How do I prove this?

    I'm thinking of proving it on a tuple level. The following document proves something similar to this, and might give you an understanding:

    Have a look at page 9 and you will see that the above rule is proven when X,Y and Z are pairwise disjoint. But I need to prove the rule as it is.

    Can someone please help me with this, or am I posting this in the wrong forum? I'm totally lost.

  2. #2
    Join Date
    Feb 2004
    In front of the computer
    If you look in your book under the transitive rule, you ought to be able to follow this from the example there. This is nearly the "poster child" for the simplest possible use of a transitive association.

    Give it a shot, post what you've got, and I'm sure that we'll be able to help you.


Posting Permissions

  • You may not post new threads
  • You may not post replies
  • You may not post attachments
  • You may not edit your posts